Examining climate change and sustainable/fast fashion in the 21st century: 'Trash the Runway'. Issue 1 (26th May 2021) - Boykoff, Maxwell; Chandler, Patrick; Church, Presley; Osnes, Beth
Abstract: We interrogate fast fashion in the 21st century in the context of a changing climate, assessing emergent trends in sustainable fashion as an alternative consumption pathway through the annual 'Trash the Runway' event in Boulder, Colorado. In this research, we interviewed and surveyed designers and analyzed workshop activities that led up to their annual fashion show. We also interviewed and surveyed students at the University of Colorado who worked with designers to produce short films about them and their work. The project centers on decolonial practice by providing —who are often marginalized in decision-making processes—a stage to articulate policy and behavior changes to address climate change and sustainability. We found designers expressed reticence before the workshops and events to speak about climate change in everyday life, yet their design work creatively spoke powerfully for them, and they expressed less discomfort after the experience, while they advanced their skillset as climate communicators. Moreover, we found both designers and student partners reported that they think climate change will impact people greatly in the future. Also, while comparatively fewer respondents reported that climate change impacts them personally, our findings showed those noting personal impacts nearly doubled after participation in the sustainable fashion project. Although engagement with sustainable fashion helps to defetishize production processes and link consumption habits with awareness of climate and environmental change, more creative work should be done through fast- and sustainable-fashion endeavors to draw out spatial and temporal considerations of climate change threats here and now.